Enabling sustainable community-based human-tiger conflict management in Seluma, Bengkulu, Indonesia - DIAH FITRI EKARINI; SRI SETIAWATI; JAMAL M. GAWI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ekarini DF, Setiawati S, Gawi JM. 2022. Enabling sustainable community-based human-tiger conflict management in Seluma, Bengkulu, Indonesia. Biodiversitas 23: 6404-6412. Human-wildlife conflict has emerged as one of the major threats to the global population of large carnivores. This condition applies to the endemic and Critically Endangered Sumatran tiger (Panthera tigris sumatrae). Although efforts to resolve conflict have been made from time to time, a sustainable solution is still very much needed, particularly given the unique characteristics of each case and area of conflict. A community-based approach to human-tiger conflict management can become a local-based solution towards a more sustainable management. This study aims to identify needs, gaps, and next steps related to collective action and sustainable community-based human-tiger conflict management in Seluma, Bengkulu, using a qualitative approach with literature review followed by semi-structure interview method. This study’s findings show that in the context of community-based human-tiger conflict management, the needs and gaps are still identified, particularly in: training and capacity building, adaptive management and applied research, communication and information exchange, policy frameworks and legal instruments, as well as funding. To make community-based human-tiger conflict management sustainable, the strength and sustainability of: coherent legal instruments; commitment, involvement, active role, communication, and support from all stakeholders, and; comprehensive environmental, social and economic data-based planning; need to be ensured.